Myocarditis and myositis/myasthenia gravis overlap syndrome induced by immune checkpoint inhibitor followed by esophageal hiatal hernia: A case report and review of the literature - Yin, Beibei; Xiao, Junjuan; Wang, Xuan; Li, Xingyu; Guan, Yaping; Chen, Jinghua; Han, Pengxi; Li, Kun; Wang, Jun (Frontiers in Medicine, 2022)
Immunotherapy with programmed death 1 (PD-1) inhibitor has shown activity as first or second line treatment for various metastatic human malignancies. Immune-related adverse events are now well described, most organ sites have been shown to be potentially influenced, but the prevalence of myocarditis and myositis/myasthenia gravis overlap syndrome following by esophageal hiatal hernia induced by immunotherapy is rarely reported. Here we described a 71-year-old women with a progressed unresectable extrahepatic cholangiocarcinoma and biliary obstruction. She had no prior history of muscle weakness and neuromuscular disease with a normal body mass index. She was treated with sintilimab as a rescue regimen of immunotherapy. After the first cycle of treatment, she experienced a grade 4 myopathy including simultaneous myositis, myalgia, and myocarditis due to multiple injuries in her cardiac, skeletal, and ocular muscles. She had elevated levels of creatine kinase, cardiac troponin I, and myoglobin, but myasthenia gravis and myositis specific and myositis-related antibodies were negative. Immunotherapy was discontinued and pulse high-dose methylprednisolone with a slow tapering and intravenous immunoglobulin was initiated. Two weeks later, the patient’s clinical presentations improved significantly. A subsequent cardiac magnetic resonance examination revealing old myocardial injury that may be a result of immune-related cardiac toxicity. In the third month following the PD-1 inhibitor therapy, she restarted with systemic chemotherapy in combination with an anti-angiogenic agent but without immunotherapy. Half a year later, she complained of repeated abdominal distension and radiographic examinations and endoscopy showed a clinically confirmed diagnosis of sliding hiatal hernia of the esophagus and gastroesophageal reflux disease. Due to mild symptoms associated with gastroesophageal reflux, she was suggested with close monitoring with acid secretion blockade rather than immediate surgical intervention. Severity for patients with myositis and myocarditis accompanied without myasthenia gravis is similar to those with myasthenia gravis. Considering the use of PD-1 inhibitor is increasing in cancer patients, physicians should therefore pay more attention to immunotherapy-induced myocarditis with myositis/myasthenia gravis overlap syndrome. Since we hypothesize diaphragmatic hiatal hernia as a potential consequence of immunotherapy-induced myositis, reports on hiatal hernias subsequently to immunotherapy-induced myositis are needed.